Inhibition of Protein Kinase CK2 Affects Thymidylate Synthesis Cycle Enzyme Level and Distribution in Human Cancer Cells - Wińska, Patrycja; Widło, Łukasz; Senkara, Elżbieta; Koronkiewicz, Mirosława; Cieśla, Jarosław M.; Krzyśko, Alicja; Skierka, Katarzyna; Cieśla, Joanna (Frontiers in Molecular Biosciences, 2022)
Thymidylate synthase (TS), dihydrofolate reductase (DHFR) and serine hydroxymethyltransferase (SHMT) constitute thymidylate synthesis cycle providing thymidylate for DNA synthesis and repair. Our previous studies indicated that TS and DHFR are the substrates of protein kinase CK2. This work has been aimed at elucidation of the effect of CK2 activity on cell cycle progression, thymidylate synthesis enzymes expression and localization, and the role of CK2-mediated TS phosphorylation in in vitro di- and trimolecular complexes formation. The results were obtained by means of western-blot, confocal microscopy, flow cytometry, quantitative polymerase chain re-action (QPCR), quartz crystal microbalance with dissipation monitoring (QCM-D) and microthermophoresis (MST). Our research indicates that CK2 inhibition does not change the levels of the transcripts, however it affects the protein levels of DHFR and TS in both tested cell lines,. i. e. A549 and CCRF-CEM, and the level of SHMT1 in CCRF-CEM cells. Moreover, we show that CK2-mediated phosphorylation of TS enables the protein (pTS) interaction with SHMT1 and causes that the tri-complex containing SHMT1, DHFR and pTS is much more stable. Our results suggest an important regulatory role of CK2-mediated phosphorylation for interaction and intracellular protein level of enzymes involved in thymidylate biosynthesis cycle.